KONCEPT SNU W CYKLU WIERSZY INNY LISNIANSKIEJ НЕПРАВИЛЬНЫЙ ВЕНОК - Nikadem-Malinowska, Ewa (Acta Neophilologica, 2012)
Metaphorisation is the basis of poetic language. The main basis of poet’s creative process is intuitive thinking. This paper is devoted to the cognitive analysis of the Inna Lisnianskaya’s cycle, due to its excessively developed concepts of sleep and dream. In the fourteen sonnets, linked together by composition and plot, the poet creates an image of a timeless reality of dreams which is composed of mythical, biblical, historical and biographical elements. Since learning is mainly based on finding similarities, Lisnianskaya combines the concepts of water, waves, sea, chaos, the ark, wine, love, life and death and builds a dreamlike world in which lyrical characters are able to handle the matters interrupted by their separation.